Analisis Kinerja Keuangan Ditinjau dari Realisasi Anggaran Belanja Tingkat Ekonomis, Efektivitas, serta Efisiensi pada BAPPEDA LITBANG Ponorogo - Lutfi Diah Ariyani; Khusnatul Zulfa Wafirotin; Iin Wijayanti (MAMEN: Jurnal Manajemen, 2022)
The budget can be referred to as an autonomous system because it has goals or targets that have been systematically designed as numbers and expressed in monetary units covering activities over a certain period of time. This study aims to analyze the realization of the expenditure budget to measure the economic level, effectiveness and efficiency of the financial performance of BAPPEDA LITBANG Ponorogo Regency. The data used in this study is secondary data in the form of a Budget Realization Report for the 2017-2021 Fiscal Year. The data analysis method used in this study is a quantitative descriptive method using the concept of Value for money in the form of measuring Economic Ratios, Effectiveness Ratios and Efficiency Ratios. Retrieval of research data used is documentation and direct observation with the head of the finance department of BAPPEDA LITBANG Ponorogo Regency. Based on the results of the research above, it can be concluded that the financial performance of BAPPEDA LITBANG Ponorogo Regency is generally said to be good. This means that BAPPEDA LITBANG Ponorogo Regency has been careful in managing the budget provided by the government and in accordance with existing needs and budgets. In addition, the management of the expenditure budget carried out by BAPPEDA LITBANG Ponorogo Regency is in accordance with applicable standards.